Molecular differentiation of Entamoeba histolytica and Entamoeba dispar from Tunisian food handlers with amoeba infection initially diagnosed by microscopy - Ben Ayed S.; Ben Abdallah R.; Mousli M.; Aoun K.; Thellier M.; Bouratbine A. (Parasite, 2008)
The purpose of the study was to obtain more reliable epidemiological data concerning Entamoeba (E.) histolytica infection in Tunisian food handlers using established molecular tools able to differentiate E. histolytica from E. dispar. From 2002 to 2005, 4,266 fresh stools specimens received in the setting of the National program of food handlers’ control were analysed by optical microscopy. Twelve (2.8 ‰) were positive for the presence of four nuclei cysts identified as E. histolytica/E. dispar. Extraction of DNA from the 12 samples, followed by specific amplifications of E. histolytica and E. dispar SSU rDNA, showed that 11 samples (92%) were positive for E. dispar and negative for E. histolytica. Sequencing analysis of 8 PCR products permitted to verify the results obtained with conventional PCR. The remaining sample was negative by PCR amplifying E. histolytica DNA or E. dispar DNA specifically, although it did not show any inhibition. It probably contains protozoan cysts genetically distinct from these two species but morphological similar. Estimation of relative proportions between E. histolytica and E. dispar in cyst carriers showed that all explored individuals harboured the non pathogenic E. dispar strains. This result highlights the need of use in this population of complementary tests that allow specific diagnosis and obviate unnecessary chemotherapy.